Molecular Control of Follicular Helper T cell Development and Differentiation - Wu, Haijing; Deng, Yaxiong; Zhao, Ming; Zhang, Jianzhong; Zheng, Min; Chen, Genghui; Li, Linfeng; He, Zhibiao; Lu, Qianjin (Frontiers in Immunology, 2018)
Follicular helper T cells (Tfh) are specialized helper T cells that are predominately located in germinal centers and provide help to B cells. The development and differentiation of Tfh cells has been shown to be regulated by transcription factors such as B-cell lymphoma 6 protein (Bcl-6), signal transducer and activator of transcription 3 (STAT3) and B lymphocyte-induced maturation protein-1 (Blimp-1). In addition, cytokines, including IL-21, have been found to be important for Tfh cell development. Moreover, some epigenetic modifications have also been reported to be involved in the determination of Tfh cell fate. The regulatory network is complicated, and the number of novel molecules identified to control the fate of Tfh cells is increasing. Therefore, this review aims to summarize the current knowledge of molecular regulation of Tfh cell development and differentiation at the protein level and at the epigenetic level, for better understanding of Tfh cell biology and providing potential targets for clinical intervention in the future.